2021
DOI: 10.3390/jcm10153385
|View full text |Cite
|
Sign up to set email alerts
|

Review of Ireland’s First Year of the COVID-19 Pandemic Impact on People Affected by Eating Disorders: ‘Behind Every Screen There Was a Family Supporting a Person with an Eating Disorder’

Abstract: Irish society went into one of the most stringent lockdowns in March 2020 due to the COVID-19 pandemic, and barring a few weeks, remains highly restricted at time of writing. This has produced a wide range of challenges for those affected by eating disorders, as well as treatment services and Bodywhys, The Eating Disorders Association of Ireland. Current research indicates that COVID-19 has impacted across three key areas—the experience of those with an eating disorder, the experience of service provision, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…N for clinical sample numbers was reported in this table. d Parsons et al's ( 2021 ) sample was recruited through the PiLaR program in Ireland, which is a program for family members supporting a loved one with an ED throughout the pandemic. Family members reported on clinical information about their loved one's ED throughout the pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…N for clinical sample numbers was reported in this table. d Parsons et al's ( 2021 ) sample was recruited through the PiLaR program in Ireland, which is a program for family members supporting a loved one with an ED throughout the pandemic. Family members reported on clinical information about their loved one's ED throughout the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies compared the differences in admissions from before the pandemic to during the pandemic, the percent changes in admissions in individual studies varied from 0% to 123%, respectively (Ayton et al, 2021 ; Graell et al, 2020 ; Hansen et al, 2021 ; Haripersad et al, 2021 ; Jones et al, 2020 ; Lin et al, 2021 ; Matthews et al, 2021 ; Otto et al, 2021 ; Parsons et al, 2021 ; Spettigue et al, 2021 ; Springall et al, 2021 ). The pooled hospital admissions across the studies demonstrated on average a 48% (pre = 591, post = 876, n = 10 studies) increase in ED admissions during the pandemic compared to previous timepoints.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 epidemic significantly impacted eating disorder (ED) patients, interfering with the recovery process [97]. Parsons et al [98] suggested that the pandemic has impacted the experience of ED patients, the experience of service provision and the family situation. Therefore, support is necessary in various forms for people with eating disorders and their families.…”
Section: Orthorexia Fear Of Covid-19 and Pa Among University Studentsmentioning
confidence: 99%
“…Despite the elevated psychological risk profiles of ED patients’ sisters, and the evidence of an increase of psychological distress in parents during the pandemic [ 16 ], to our knowledge, no study has considered this specific population in the evaluation of the effects of COVID-19; instead, they have focused solely on parents or caregivers [ 16 , 24 ]. However, literature has shown that comparing ED patients and their sisters enable the evaluation of intra- and interpersonal moderating factors for the impacts of EDs [ 23 ].…”
Section: Introductionmentioning
confidence: 99%